Conference Review - The European Association for Terminology, Third Terminology Summit, Brussels - Grinsted, Annelise (Language at Work - Bridging Theory and Practice, 2007)
The European Association for Terminology held its Third Summit in Brussels on the 13th and 14th of November, 2006. It was a special summit due to the fact that it was also the celebration of the 10th anniversary of the European Association for Terminology.